A randomized controlled study of a combination of internal and external treatments for albumin paclitaxel-related peripheral neurotoxicity: A randomized controlled: A study protocol. Issue 51 (23rd December 2022) - Li, Xiaoli; Sun, Qimeng; Ding, Hao; Hao, Shulan; Lan, Yonglin; Liu, Likun; Wang, Ruimin
Abstract : Introduction: Albumin-bound paclitaxel (nab-PTX), a novel paclitaxel preparation, has been found to successfully blocks tumor progression in breast and lung cancer. However, at the same time of as clinical application, neurotoxicity caused by nab-PTX has become the main factor limiting the clinical application of nab-PTX, which seriously affects the quality of life of patients and increases their psychological or financial burden. In clinical applications, JHGWD combined with bloodletting therapy at the end of the extremities has a positive effect on neurotoxic symptoms such as numbness, pain, and weakness of the hands and feet caused by nab-PTX. In a single-arm experiment, it was also found that the immediate effective rate of exsanguination therapy was as high as 70%, and when combined with oral Chinese medicine treatment, it further improved the efficacy. Therefore, a randomized controlled trial (RCT) was designed to further evaluate the efficacy and safety of this treatment. Methods: This RCT will be conducted at the Shanxi Provincial Hospital of Traditional Chinese Medicine. A total of 120 patients with Nab-PTX chemotherapy-induced neurotoxicity will be recruited. Treatment groups will be categorized into herbs alone group, bloodletting treatment alone group, and herbs combined with bloodletting group. Blank control was used. The primary outcome will be the EORTC QLQ-CIPN20 scale of the included patients, and the secondary outcomes will include EMG, peripheral neurotoxicity symptom score, NCI-CTCAE5.0 peripheral neurotoxicity grade, and WHO anti-tumor drug peripheral neurotoxicity grade. Adverse reactions will be recorded throughout the process. All data in this RCT will be analyzed by SPSS 26.0 software. Discussion: The results of this RCT will contribute to treating PIPN, relieving the neurotoxic symptoms, and improving the quality of life of patients. Finally, the RCT results will be published in a relevant academic journal on completion of the trial. Trial registration: ChiCTR2200060217(May22, 2022)